Studies on the Utilization of Oscillatoria thiebautii as Food Source for Artemia sp Culture: Short Communication - Shah, S. G. Abbas; Sultana, Razia; Askari, Abid (Biological Sciences - PJSIR, 2005)
Growth and population of a native parthenogenetic Artemia sp in relation to Oscillatoria thiebautii was studied. O. thiebautii was inoculated to confirm its utilization in the Artemia sp culture. The study was carried out between October-July when the temperature ranged between 16-30 °C. The culture salinity and pH was maintained at 50 ppt and 8±1, respectively. The Artemia, at these culture conditions, showed good growth and survival in the presence of O. thiebautii as its food source. The study indicates O. thiebautii as a cost-effective feed for Artemia sp culture, which is both inexpensive and available in abundance.